The Effectiveness of Recognizing the Existence of Traditional Institutions in Indonesia Based on The Constitution - Asfia, Hilyatul; Wijaya, Andika; D. Bangas, Karlinae; Milionhart, Benaya (Sahabat Publikasi, 2024)
Plurality is a social fact that cannot be avoided in Indonesia. The diversity of Indonesian people's tribes, religions, races, languages ??and religions shows their diversity. The founders of the Republic of Indonesia used the basic philosophy of